PREDATORY JOURNALS: SCIENTIFIC PIRATES - Rojas-Valerde, Daniel (2018)
The researchers worldwide have multiple alternatives to publish and disseminate their scientific productions. Hand in hand with the technological development, journals have digitalized their productions; this has been utilized by different pseudoacademic companies to offer their services for profit. This paper will offer some clues to differentiate the journals with quality standards from the so-called predatory journals.